Nitrogen-doped asphalt-based hard carbon material as well as preparation method and application thereof
By oxidizing and doping the asphalt, nitrogen-doped asphalt-based hard carbon materials are prepared, which solves the problem of insufficient rate and capacity performance of existing materials, and achieves higher electrochemical performance and sodium ion adsorption capacity.
Patent Information
- Application Number
- CN202411752015.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-02
- Publication Date
- 2025-03-14
AI Technical Summary
There is still room for improvement in the rate performance and capacity performance of existing asphalt-based hard carbon materials in sodium ion batteries.
By oxidation and nitrogen doping treatment on the asphalt, pyridine nitrogen or pyrrole nitrogen is introduced to form a nitrogen-doped asphalt-based hard carbon material. The method includes oxidation of the asphalt, then mixing with the nitrogen-containing compound for nitrogen doping treatment, and finally pre-carbonization and carbonization treatment to prepare a nitrogen-doped asphalt-based hard carbon material.
The rate performance and capacity of asphalt-based hard carbon materials are improved, the adsorption capacity of sodium ions is enhanced, and the electrochemical performance is improved.
Smart Images

Figure CN119612485A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of battery materials, and in particular relates to a nitrogen-doped asphalt-based hard carbon material and a preparation method and application thereof. Background Art
[0002] In recent decades, the rapid development of lithium-ion batteries has made it the most important energy storage device in daily life. However, lithium resources are limited and costly, while sodium resources are abundant and cost-effective. As a result, sodium-ion batteries have gradually received attention and attention. The performance of sodium-ion batteries depends to a large extent on the electrode materials. As a key component of sodium-ion batteries, the negative electrode has an important impact on the practicality and cost of sodium-ion batteries. In the field of sodium-ion batteries, carbon-based materials, titanium-based materials, alloys, organic compounds, etc. are often used for the negative electrode. Among them, carbon-based materials have the advantages of high cost-effectiveness, high abundance, and adjustable structure. They are very promising negative electrode materials for sodium-ion batteries. Hard carbon is a highly amorphous structure with short-range graphitization. Compared with the graphite structure, the interlayer distance (0.37-0.42nm) of hard carbon is larger, with abundant voids or pores, and abundant defects.
[0003] The precursor materials of hard carbon negative electrode materials for sodium ion batteries are mainly divided into four types: biomass precursors, sugar precursors, synthetic resin precursors, and asphalt precursors. Asphalt-based precursors have the advantages of low cost, high carbon content, and high carbon yield, and are considered to be potential carbon sources for synthetic carbon negative electrodes. Asphalt is a byproduct of the coal or petroleum industry. It is mainly composed of a large number of polycyclic aromatic hydrocarbons (PAHs) and structurally related heterocyclic compounds. It has a low price and low ash content. It can be used to form nearly parallel carbon layers during heating to ensure high carbon yield and conductivity. However, direct pyrolysis of asphalt forms a microstructure with small interlayer spacing and high orientation during the uncontrollable liquid phase carbonization process, resulting in poor rate performance of sodium ion batteries. Existing technologies can interfere with the graphitization of asphalt and drive the transformation of the microstructure by modifying asphalt molecules to weaken or destroy the interaction between aromatics. Therefore, asphalt molecule modification strategies are gradually applied to high-performance negative electrode materials. Model compounds such as quinoline or isoquinoline in pitch can be used to prepare porous carbon under the catalysis of proton acid (HF / BF3) and Lewis acid (AlCl3) to improve electrochemical performance. At the same time, asphalt and cross-linked resins (phenolic, polyformaldehyde and furfuryl alcohol resins) or polymers (polypropylene, polysaccharides and butadiene-styrene copolymers) are co-carbonized to form disordered carbon with a high microporous structure. However, the capacity and rate performance of existing pitch-based hard carbon materials need to be further improved. Summary of the invention
[0004] The present invention aims to solve at least one of the technical problems existing in the above-mentioned prior art. To this end, the present invention provides a nitrogen-doped pitch-based hard carbon material and a preparation method and application thereof. The pitch-based hard carbon material prepared by the preparation method of the present invention has high rate performance and capacity.
[0005] A first aspect of the present invention provides a method for preparing a nitrogen-doped pitch-based hard carbon material.
[0006] Specifically, a method for preparing a nitrogen-doped pitch-based hard carbon material comprises the following steps:
[0007] The asphalt is oxidized to obtain oxidized asphalt;
[0008] Performing nitrogen doping treatment on the oxidized asphalt to obtain an asphalt hard carbon precursor;
[0009] Pre-carbonizing and carbonizing the pitch-based hard carbon precursor to obtain the pitch-based hard carbon material;
[0010] A nitrogen-containing compound is used in the nitrogen-doping process, and the nitrogen-containing compound includes a pyridine group and / or a pyrrol group, and a hydroxyl group and / or an aldehyde group.
[0011] The second aspect of the present invention provides a nitrogen-doped pitch-based hard carbon material prepared by the above-mentioned preparation method.
[0012] The third aspect of the present invention provides an application of a nitrogen-doped pitch-based hard carbon material, and specifically relates to a sodium ion battery, comprising the nitrogen-doped pitch-based hard carbon material.
[0013] Compared with the prior art, the beneficial effects of the present invention are as follows:
[0014] The preparation method of the present invention is to oxidize the asphalt so that the asphalt contains rich oxygen-containing groups (such as hydroxyl groups and aldehyde groups). During the nitrogen doping process, pyridine nitrogen (or pyrrole nitrogen) is introduced into the oxidized asphalt through the hydroxyl aldehyde reaction, thereby improving the capacity and rate performance of the asphalt-based hard carbon material.
[0015] Among them, during the nitrogen doping process, nitrogen atom doping can adjust the electron density by destroying the π-π conjugated system of oxidized asphalt and forming electronegative functional groups that enhance sodium affinity. The nitrogen atoms in the asphalt-based hard carbon material exist in the form of pyridinic nitrogen (or pyrrolic nitrogen) and graphitic nitrogen (wherein, graphitic nitrogen is obtained by converting part of the pyridinic nitrogen or pyrrolic nitrogen during the carbonization process). In addition to providing an electron to the conjugated π bond system, pyridinic nitrogen also has a pair of lone pairs of electrons, which can not only improve the conductivity of the asphalt-based hard carbon material, but also increase the slope capacity by introducing more active sites. Pyridinic nitrogen or pyrrolic nitrogen can increase the adsorption of sodium ions. According to the "adsorption-insertion" theory, the introduction of pyridinic nitrogen or pyrrolic nitrogen can increase the slope ratio, thereby improving the rate performance of the asphalt hard carbon material.
[0016] In addition, the introduction of pyridinic nitrogen or pyrrolic nitrogen can expand the interlayer distance and increase defects compared to the introduction of graphitic carbon.
[0017] Nitrogen doping can also introduce defects during the carbonization process of the pitch hard carbon precursor and regulate the disordered structure of the pitch hard carbon material, which can hinder the effective development of long-range ordered carbon and the accumulation of graphite sheets, and provide sufficient active sites for the adsorption of sodium ions. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 The charge and discharge curves of button batteries assembled from asphalt-based hard carbon materials of Example 1 and Comparative Example 1;
[0019] Figure 2 This is a rate performance diagram of button cells assembled from asphalt-based hard carbon materials of Example 1 and Comparative Example 1. DETAILED DESCRIPTION
[0020] The technical solutions in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, rather than all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by those skilled in the art without making creative work belong to the scope of protection of the present application. In addition, it should be understood that the specific implementation methods described herein are only used to illustrate and explain the present application, and are not used to limit the present application.
[0021] In the description of the present application, the term "including" means "including but not limited to". Various embodiments of the present invention may be presented in the form of a range; it should be understood that the description in the form of a range is only for convenience and brevity, and should not be understood as a rigid limitation on the scope of the present invention; therefore, the range description should be considered to have specifically disclosed all possible sub-ranges and single numerical values within the range. For example, the range description from 1 to 6 should be considered to have specifically disclosed sub-ranges, such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., as well as single numbers within the range, such as 1, 2, 3, 4, 5 and 6, regardless of the range. In addition, whenever a numerical range is indicated herein, it is meant to include any cited number (fractional or integer) within the indicated range.
[0022] In this application, "and / or" describes the association relationship of associated objects, indicating that there may be three relationships. For example, A and / or B can mean: A exists alone, A and B exist at the same time, and B exists alone. A and B can be singular or plural.
[0023] In the present application, "at least one", "at least one" and other similar descriptions specifically refer to one or more, one or more; "multiple", "multiple" and other similar descriptions specifically refer to two or more, two or more. "At least one", "at least one of the following" or similar expressions refer to any combination of these items, including any combination of single or plural items. For example, "at least one of a, b, or c", or "at least one of a, b, and c" can all represent: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, c can be single or plural, respectively.
[0024] A first aspect of the present invention provides a method for preparing a nitrogen-doped pitch-based hard carbon material, comprising the following steps:
[0025] The asphalt is oxidized to obtain oxidized asphalt;
[0026] Performing nitrogen doping treatment on the oxidized asphalt to obtain an asphalt hard carbon precursor;
[0027] Pre-carbonizing and carbonizing the pitch-based hard carbon precursor to obtain the pitch-based hard carbon material;
[0028] A nitrogen-containing compound is used in the nitrogen-doping process, and the nitrogen-containing compound includes a pyridine group and / or a pyrrol group, and a hydroxyl group and / or an aldehyde group.
[0029] Specifically, the present invention provides a method for preparing a nitrogen-doped pitch-based hard carbon material, comprising the following steps:
[0030] Step S11: oxidizing the asphalt to obtain oxidized asphalt;
[0031] Step S12: mixing the oxidized asphalt with a nitrogen-containing compound, adding a catalyst to perform nitrogen-doping treatment, and obtaining an asphalt hard carbon precursor;
[0032] Step S13: placing the pitch hard carbon precursor under a protective gas atmosphere, performing pre-carbonization and carbonization treatments to obtain the pitch-based hard carbon material.
[0033] The present invention first performs oxidation treatment on asphalt, so that the asphalt contains abundant oxygen-containing groups, such as hydroxyl groups and aldehyde groups. During the nitrogen doping process, nitrogen-containing compounds are added, and the nitrogen-containing compounds include pyridyl groups and / or pyrrole groups, as well as hydroxyl groups and / or aldehyde groups. The nitrogen-containing compounds react with the oxidized asphalt through hydroxyl-aldehyde reaction to introduce pyridine nitrogen (and / or pyrrole nitrogen) into the oxidized asphalt, and then the asphalt-based hard carbon material is prepared through pre-carbonization and carbonization treatment. The asphalt-based hard carbon material has high capacity and good rate performance.
[0034] In step S11:
[0035] In some embodiments of the present invention, the oxidation treatment includes oxidation treatment in an oxygen-containing gas atmosphere or oxidation treatment by adding an oxidant other than oxygen. The oxidation treatment may be a conventional oxidation process, which serves to introduce oxygen-containing groups, such as aldehyde groups, hydroxyl groups, etc., into the asphalt.
[0036] In some embodiments of the present invention, the asphalt includes coal tar or petroleum tar. The use of coal tar helps to reduce production costs. Further, the softening point of the asphalt is not less than 150°C, for example, the softening point is 200-300°C, more specifically, for example, 150°C, 200°C, 280°C, 300°C. The sulfur content of the asphalt is less than 0.1wt% (wt% means weight percentage), for example, 0.01wt%-0.08wt%. Low sulfur content is conducive to reducing the adverse effects of impurities on the electrochemical properties of asphalt-based hard carbon materials.
[0037] In some embodiments of the present invention, the D of the asphalt 50 Less than or equal to 10 μm. For example, less than or equal to 6 μm, specifically 1 μm, 5 μm, 6 μm, 9 μm. Smaller particle size helps to increase the contact area between asphalt and peroxynitric acid substances, making the reaction more complete.
[0038] In some embodiments of the present invention, the oxidation treatment process is to mix asphalt with a solvent to obtain a suspension, and then spray oxidize it in an air atmosphere to obtain oxidized asphalt. The asphalt is fully oxidized by spray oxidation, so that the content of oxygen-containing groups in the oxidized asphalt is increased, which is conducive to improving the uniformity of nitrogen doping.
[0039] The solvent may include xylene and gasoline, for example, xylene and gasoline are mixed in a volume ratio of 1:(0.5-2.5) to form the solvent. Specifically, xylene and gasoline are mixed in a volume ratio of 1:1 or 1:2 to form the solvent.
[0040] In some embodiments of the present invention, the mass ratio of asphalt to solvent is 1:(2-5), specifically 1:2, 1:3, 1:4 or 1:5.
[0041] It can be understood that the asphalt and the solvent are mixed in a common manner in the art, such as mechanical stirring mixing or ultrasonic mixing or a combination of one or more of the above.
[0042] In some embodiments of the present invention, the temperature of the spray oxidation is 200-230° C., for example, 200° C., 210° C., 220° C., 230° C. At this temperature, it is helpful to introduce abundant oxygen-containing groups such as aldehyde groups and hydroxyl groups into the asphalt.
[0043] In some embodiments of the present invention, a spray drier can be used to carry out the spray oxidation process. Specifically, the spray air inlet temperature can be 200-230°C.
[0044] In step S12:
[0045] In some embodiments of the present invention, the nitrogen-containing compound includes at least one pyridine group and / or at least one pyrrol group, and also contains at least one hydroxyl group and / or at least one aldehyde group, and does not contain any heteroatoms other than nitrogen, oxygen, hydrogen, and carbon; in other words, the nitrogen-containing compound only contains nitrogen, oxygen, hydrogen, and carbon, which can avoid the introduction of other heteroatoms leading to a decrease in the capacity and rate performance of the asphalt-based hard carbon material.
[0046] In some embodiments of the present invention, the nitrogen-containing compound is selected from at least one of N-hydroxyethylpyrrolidine, 6-acetylpyridinecarbonitrile, 2-pyridinecarboxaldehyde, and 2,4-dimethyl-5-formylpyrrole-3-carboxylic acid. These selected nitrogen-containing compounds react with oxidized asphalt to introduce pyridine nitrogen (and / or pyrrole nitrogen) into the oxidized asphalt through an hydroxyaldehyde reaction to improve the capacity and rate performance of asphalt-based hard carbon materials. Specifically, the introduction of pyridine nitrogen or pyrrole nitrogen can increase the adsorption of sodium ions. According to the "adsorption-insertion" theory, the introduction of pyridine nitrogen or pyrrole nitrogen can increase the slope ratio and improve the rate performance of asphalt hard carbon materials. Nitrogen doping can also introduce defects in the carbonization process of the asphalt hard carbon precursor and adjust the disordered structure of the asphalt hard carbon material, which can hinder the effective development of long-range ordered carbon and the accumulation of graphite sheets, and provide sufficient active sites for the adsorption of sodium ions, thereby improving the capacity.
[0047] In some embodiments of the present invention, the catalyst includes an acid or a base, such as hydrochloric acid, nitric acid, acetic acid, sodium hydroxide, potassium hydroxide, lithium hydroxide, and more specifically, the catalyst is a hydrochloric acid or sodium hydroxide solution with a mass fraction of 5% to 10%. Under the action of the catalyst, the reaction of the oxidized asphalt and the nitrogen-containing compound at room temperature is facilitated.
[0048] In some embodiments of the present invention, the mass of the nitrogen-containing compound is 5%-20% of the mass of the oxidized asphalt, specifically, for example, 5%, 10%, 15%, or 20%.
[0049] In some embodiments of the present invention, the volume ratio of the catalyst to the total volume of the nitrogen-containing compound and the oxidized asphalt is 1: (1-3), for example, 1: 1, 1.5: 1, 2: 1. Within this range, the reaction speed can be accelerated. If the amount of the catalyst is too small, the reaction speed is slow. If the amount of the catalyst is too large, the amount of the nitrogen-containing compound and the oxidized asphalt is too small, which is not conducive to the preparation of the target product and increases the cost.
[0050] In some embodiments of the present invention, after adding the catalyst, ultrasonic treatment is performed for 0.5-2 hours, for example, 0.5, 1, or 2 hours. The conditions of ultrasonic treatment are conducive to the reaction or nitrogen doping process.
[0051] In some embodiments of the present invention, after the ultrasonic treatment, the reacted material is washed with water to a pH of 6.8-7, and then dried to obtain a pitch-based hard carbon precursor. Washing with water to neutrality can remove the added acid or alkali catalyst or other impurities, and can also reduce the ash content in the pitch-based hard carbon material.
[0052] In some embodiments of the present invention, the drying temperature of the drying treatment after water washing is 100-140° C. For example, 100° C., 110° C., 120° C., 130° C., 140° C. The drying treatment can be performed by vacuum drying or by using a spray dryer.
[0053] In step S13:
[0054] The protective gas includes nitrogen or a rare gas. The rare gas is, for example, one of argon, helium, and krypton. It is understood that the present invention may refer to the description herein for any use of a protective gas.
[0055] In some embodiments of the present invention, the pre-carbonization treatment is carried out at a holding temperature of 700-900° C., for example, 750-850° C. The pre-carbonization treatment is carried out for a holding time of 1-5 hours, for example, 2-4 hours.
[0056] In some embodiments of the present invention, during the pre-carbonization process, the temperature is increased to 700-900° C. at a heating rate of 1-5° C. / min, that is, the rate of heating to the holding temperature is 1-5° C. / min.
[0057] In some embodiments of the present invention, after the pre-carbonization treatment is completed, the obtained pre-carbonized material is crushed. For example, crushed to D 50 To 1-10μm, more specific D 50 2μm, 3μm, 4μm, 5μm, 6μm, 7μm, 8μm, 9μm, and 10μm.
[0058] In some embodiments of the present invention, the carbonization treatment is carried out at a holding temperature of 1200-1700° C. for 2-4 hours. Specifically, the carbonization holding temperature may be 1200-1300° C., 1300-1500° C., 1500-1700° C., etc. The carbonization time may be 2-3 hours, 3-4 hours, etc.
[0059] In some embodiments of the present invention, during the carbonization process, the temperature is increased to 1200-1700° C. at a heating rate of 1-5° C. / min.
[0060] In some embodiments of the present invention, after step S13, that is, after the carbonization treatment is completed, a coating treatment is further included, and the coating treatment process includes: mixing the material after the carbonization treatment with the coating asphalt, and then heating and coating the material under a protective gas atmosphere to obtain an asphalt-based hard carbon material. The coating treatment can reduce the surface defects of the material obtained after the carbonization, thereby improving the electrochemical performance of the asphalt-based hard carbon material (for example, improving the charge specific capacity).
[0061] Specifically, the coating asphalt can be selected from petroleum asphalt with a softening point of 220-280° C. The weight of the coating asphalt used is 5%-11% of the weight of the material after the carbonization treatment. For example, 5%-10%. Specifically, for example, 5%, 10%, 11%.
[0062] In some embodiments of the present invention, the heat-coating treatment is carried out at a holding temperature of 1200-1700° C. for 1-3 hours. Further, the heat-coating treatment is carried out at a holding temperature of 1300-1500° C. for 0.5-1.5 hours.
[0063] In some embodiments of the present invention, the heating and coating process further includes a crushing process, wherein the material after the carbonization process and the coated asphalt are mixed and crushed to D 50 The thickness is 2-8 μm, for example, 3-8 μm, more specifically, 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, and 8 μm.
[0064] A second aspect of the present invention provides a nitrogen-doped pitch-based hard carbon material, which is prepared by the method for preparing a nitrogen-doped pitch-based hard carbon material provided by the present invention.
[0065] The third aspect of the present invention provides an application of a nitrogen-doped asphalt-based hard carbon material, which can be specifically applied to sodium ion batteries, for example, as a negative electrode material of a sodium ion battery.
[0066] Unless otherwise specified, the raw materials, reagents or devices used in the following examples can be obtained from conventional commercial sources or by existing known methods.
[0067] Example 1
[0068] A method for preparing a nitrogen-doped pitch-based hard carbon material, comprising:
[0069] Step (1): Asphalt spray oxidation treatment
[0070] A certain amount of asphalt (coal tar with sulfur content less than 0.1wt% and softening point of 200°C) is crushed and sieved (the mesh number of the sieve during sieving is 200 meshes), the sieved material is mixed with a mixed solvent of xylene and gasoline (volume ratio of 1:1) in a mass ratio of 1:3 to form a suspension, and the suspension is subjected to spray oxidation treatment using a spray dryer in an air atmosphere at a spray oxidation temperature of 200°C to obtain oxidized asphalt;
[0071] Step (2): Nitrogen doping
[0072] The oxidized asphalt and N-hydroxyethyl pyrrolidine were fully mixed, the mass of N-hydroxyethyl pyrrolidine was 10% of the mass of the oxidized asphalt, and 10% of dilute hydrochloric acid was added at room temperature, which was equal to the total volume of the oxidized asphalt and N-hydroxyethyl pyrrolidine, and ultrasonically treated for 2 hours, and then washed with water until the pH was 7, and the washed material was dried using a spray dryer at a drying temperature of 100°C to obtain an asphalt hard carbon precursor;
[0073] Step (3): Pre-carbonization
[0074] The asphalt hard carbon precursor obtained in step (2) is added into a carbonization furnace, and heated to 700°C at a heating rate of 5°C / min under the protection of an inert gas (argon) for 4 hours, and the cooled block is crushed to obtain a pre-carbonized material powder;
[0075] Step (4): Carbonization
[0076] The pre-carbonized material powder obtained in step (3) is placed in a carbonization furnace, and heated to 1300° C. at a heating rate of 2° C. / min under the protection of an inert gas (argon) and kept warm for 2 h to obtain a powdered carbon material;
[0077] Step (5): High temperature coating
[0078] The carbon material obtained in step (4) is mixed with coated asphalt (the coated asphalt is petroleum asphalt with a softening point of 220°C, and the weight of the coated asphalt is 10% of the carbon material), and the mixture is fully crushed and mixed in a powder mill, and the particle size D50 is controlled between 6-8μm. The mixture is then placed in a tubular furnace, heated to 1300°C under the protection of an inert gas (argon) and coated for 1 hour to obtain an asphalt-based hard carbon material.
[0079] Example 2
[0080] Compared with Example 1, the only difference is that step (1) is different, and the other steps are the same as Example 1.
[0081] The specific contents of step (1) of Example 2 are as follows:
[0082] Take a certain amount of asphalt (coal tar with a sulfur content of less than 0.1wt% and a softening point of 200°C), crush it, sieve it, put the screened material into a muffle furnace, heat it to 200°C at a heating rate of 2°C / min for oxidation treatment, and keep it at 200°C for 6h.
[0083] Example 3
[0084] Compared with Example 1, the only difference of Example 3 is that Example 3 does not include step (5), and the rest of the process is the same as Example 1.
[0085] Example 4
[0086] Compared with Example 1, the only difference of Example 4 is that in step (2) of Example 4, an equal amount of 6-acetylpyridinecarbonitrile is used to replace the N-hydroxyethylpyrrolidine in Example 1, and the rest of the process is the same as Example 1.
[0087] Example 5
[0088] Compared with Example 1, the only difference of Example 5 is that in step (2) of Example 5, the mass of N-hydroxyethyl pyrrolidine is 5% of the mass of the oxidized asphalt, and the rest of the process is the same as that of Example 1.
[0089] Example 6
[0090] Compared with Example 1, the only difference of Example 6 is that in step (2) of Example 5, the mass of N-hydroxyethyl pyrrolidine is 20% of the mass of the oxidized asphalt, and the rest of the process is the same as Example 1.
[0091] Comparative Example 1
[0092] Compared with Example 1, the difference of Comparative Example 1 is that Comparative Example 1 does not include step (2), that is, Comparative Example 1 does not perform nitrogen doping treatment, and the rest of the process is the same as that of Example 1.
[0093] Comparative Example 2
[0094] Compared with Example 1, the difference of Comparative Example 2 is that in step (2) of Comparative Example 2, an equal amount of urea is used to replace the N-hydroxyethylpyrrolidine in Example 1, and the rest of the process is the same as Example 1.
[0095] Comparative Example 3
[0096] Compared with Example 1, the difference of Comparative Example 3 is that in step (2) of Comparative Example 3, an equal amount of methylimidazole dicyanamide is used to replace the N-hydroxyethylpyrrolidine in Example 1, and the rest of the process is the same as Example 1.
[0097] Product effect testing
[0098] The asphalt-based hard carbon materials obtained in the above Examples 1-6 and Comparative Examples 1-3 were respectively prepared into button-type batteries.
[0099] The specific steps for preparing button batteries are as follows: asphalt-based hard carbon material is mixed with conductive carbon Super-P and PVDF (polyvinylidene fluoride) in a mass ratio of 92:4:4, and then N-methylpyrrolidone (NMP) is used as solvent. After mixing evenly, it is coated on aluminum foil and dried in a vacuum oven at 102°C. After rolling, it is cut into circular electrode sheets with a diameter of 8 mm, with sodium sheets as the negative electrode, the electrolyte is NaPF6 ester electrolyte of model NP-001, and the diaphragm is a glass fiber diaphragm. The button batteries are assembled in a glove box filled with argon.
[0100] The charge and discharge performance of the prepared button battery was tested. The battery test adopted the Xinwei battery test system. The test method adopted constant current and constant voltage discharge and constant current charging. The charge and discharge test was carried out at a current density of 0.1C. The discharge cut-off voltage was 0V and the charge cut-off voltage was 2.5V. The results are shown in Table 1.
[0101] During the discharge process, the voltage drops from 2.5V to 0V, wherein the discharge capacity corresponding to the voltage dropping from 2.5V to 0.1V is recorded as the ramp capacity, and then the ramp capacity is divided by the entire discharge capacity*100%=ramp capacity ratio.
[0102] The rate performance of the button cell prepared in Example 1 was tested. The battery test adopted the Xinwei battery test system. The test method adopted constant current charge and discharge. The charge and discharge tests were carried out at current densities of 0.1C, 0.5C, 1C, and 5C respectively. The discharge cut-off voltage was 0V, and the charge cut-off voltage was 2.5V.
[0103] Table 1
[0104] Charge specific capacity (mAh / g) Charge and discharge efficiency (%) Ramp capacity ratio (%) Example 1 318.73 86.62 43.65 Example 2 313.69 86.43 42.46 Example 3 319.19 84.13 44.68 Example 4 316.58 86.4 42.89 Example 5 316.78 86.35 41.78 Example 6 314.65 84.78 43.95 Comparative Example 1 294.02 87.1 34.66 Comparative Example 2 304.89 86.86 39.52 Comparative Example 3 293.59 86.4 34.15
[0105] It can be seen from Table 1 that the charging specific capacities corresponding to Examples 1-6 of the present invention are significantly higher than those of Comparative Examples 1-3.
[0106] It can be seen from Example 1 and Comparative Examples 1-3 that when no nitrogen doping treatment is performed or the type of nitrogen-containing compound is changed, the charge specific capacity corresponding to the asphalt-based hard carbon material prepared in Comparative Examples 1-3 will be significantly reduced, and the slope capacity ratio will also be significantly reduced. It can be seen that the nitrogen-containing compound used in Example 1 introduces pyrrole nitrogen into the asphalt-based hard carbon material, which helps to improve the charge specific capacity and slope capacity ratio of the asphalt-based hard carbon material.
[0107] from Figure 1 It can be seen that Example 1 is nitrogen-doped relative to Comparative Example 1, so that the asphalt-based hard carbon material has a higher charge specific capacity during the charge and discharge process.
[0108] from Figure 2It can be seen that Example 1 is nitrogen-doped relative to Comparative Example 1, so that the pitch-based hard carbon material has better rate performance during the charge and discharge process. This further proves that the nitrogen-doping process of the present invention can improve the specific capacity and rate performance of the pitch-based hard carbon material.
Claims
1. A method for preparing a pitch-based hard carbon material, characterized in that: The following steps are involved: The asphalt is oxidized to obtain oxidized asphalt; Performing nitrogen doping treatment on the oxidized asphalt to obtain an asphalt hard carbon precursor; Pre-carbonizing and carbonizing the pitch-based hard carbon precursor to obtain the pitch-based hard carbon material; A nitrogen-containing compound is used in the nitrogen-doping process, and the nitrogen-containing compound includes a pyridine group and / or a pyrrol group, and a hydroxyl group and / or an aldehyde group.
2. The preparation method according to claim 1, characterized in that: The oxidation treatment includes oxidation treatment in a gas atmosphere containing oxygen or oxidation treatment by adding an oxidant other than oxygen; Alternatively, the oxidation treatment process is to mix the asphalt with a solvent to obtain a suspension, and then spray-oxidize it in an air atmosphere to obtain the oxidized asphalt.
3. The preparation method according to claim 2, characterized in that: The asphalt includes coal asphalt or petroleum asphalt; and / or, the D of the asphalt 50 Less than or equal to 10μm; and / or, the solvent comprises xylene and gasoline; and / or, the mass ratio of the asphalt to the solvent is 1:(2-5); And / or, the temperature of the spray oxidation is 200-230°C; And / or, the spray oxidation process uses a spray dryer.
4. The preparation method according to claim 1, characterized in that: The nitrogen-doping process includes: mixing the oxidized asphalt with a nitrogen-containing compound, adding a catalyst for nitrogen-doping, and obtaining the asphalt hard carbon precursor; The nitrogen-containing compound includes at least one pyridine group and / or at least one pyrrol group, and also includes at least one hydroxyl group and / or at least one aldehyde group, and does not contain other heteroatoms except nitrogen, oxygen, hydrogen and carbon elements.
5. The preparation method according to claim 4, characterized in that: The nitrogen-containing compound is selected from at least one of N-hydroxyethylpyrrolidine, 6-acetylpyridinecarbonitrile, 2-pyridinecarboxaldehyde, and 2,4-dimethyl-5-formylpyrrole-3-carboxylic acid; and / or, the catalyst comprises an acid or a base; and / or, the mass of the nitrogen-containing compound is 5%-20% of the mass of the oxidized asphalt; and / or, the ratio of the volume of the catalyst to the total volume of the nitrogen-containing compound and the oxidized asphalt is 1:(1-3); And / or, after adding the catalyst, ultrasonic treatment is performed for 0.5-2h.
6. The preparation method according to claim 5, characterized in that: After the ultrasonic treatment is completed, the reacted material is washed with water until the pH value is 6.8-7, and then dried to obtain the asphalt hard carbon precursor; And / or, the pre-carbonization treatment is carried out at a holding temperature of 700-900°C; And / or, the pre-carbonization treatment is carried out for a holding time of 1-5 hours; And / or, during the pre-carbonization treatment, the temperature is increased to 700-900° C. at a heating rate of 1-5° C. / min; and / or, after the pre-carbonization treatment is completed, the obtained pre-carbonized material is crushed; And / or, the carbonization treatment is carried out at a holding temperature of 1200-1700° C. and a holding time of 2-4 hours; And / or, during the carbonization treatment, the temperature is increased to 1200-1700° C. at a heating rate of 1-5° C. / min.
7. The preparation method according to claim 1, characterized in that: After the carbonization treatment is completed, a coating treatment is also included. The coating treatment process includes: mixing the material after the carbonization treatment with coating asphalt, and then heating and coating under a protective gas atmosphere to obtain an asphalt-based hard carbon material.
8. The preparation method according to claim 7, characterized in that: The softening point of the coated asphalt is petroleum asphalt of 220-280°C; and / or, the weight of the coated asphalt is 5%-11% of the weight of the material after the carbonization treatment; And / or, the heating and coating treatment further includes a crushing treatment before the carbonization treatment, wherein the material mixed with the coated asphalt is crushed to D 50 3-8μm; And / or, the temperature of the heating coating treatment is 1200-1700° C., and the time is 1-3 hours.
9. A pitch-based hard carbon material, characterized in that: The invention is prepared by the preparation method according to any one of claims 1 to 8.
10. A sodium ion battery, characterized in that: Includes the pitch-based hard carbon material as described in claim 9.
Citation Information
Cited By
Pre-oxidized asphalt synergistically-coated double-layer hard carbon negative electrode material, preparation method thereof and sodium ion battery
CN121565820A
Preparation method, product and application of asphalt-based hard carbon material
CN121823525A